The Influence Of Corn Flour Substitution On The Quality Of Dry Noodles - Agustianingsih, Vira; Holinesti, Rahmi; Faridah, Anni; Mustika, Sari (Universitas Negeri Padang, 2024)
The use of corn flour contains various essential components such as a source of plant-based vitamin A, also known as beta-carotene content, essential fatty acids, protein, carbohydrates, and high dietary fiber. However, the utilization of local corn flour is not maximized in the food industry, as it is mainly focused on supplying animal feed, even though corn is one of Indonesia's staple commodities in supporting the national food security program. The use of corn flour can replace synthetic coloring agents with a natural yellow color obtained from the use of local corn flour derived from the beta-carotene pigment contained in corn. This research aims to analyze the influence of substituting corn flour by 0% (X0), 20% (X1), and 40% (X2) on the quality of dry noodles in terms of color, aroma, texture, and taste. The research design used was a pure experiment with a Completely Randomized Design (CRD) method. The data used were obtained directly from three limited panelists using the organoleptic evaluation format for the quality of dry noodles with corn flour substitution. The collected data were then tabulated in table format, and an Analysis of Variance (ANOVA) was conducted. If the analysis of variance shows Fcount > Ftable, then Duncan's test was carried out. The results of the research indicate a significant influence of corn flour substitution at 0% (X0), 20% (X1), and 40% (X2) on the quality of color (pale yellow), and texture (chewy). The best result was observed at the 20% substitution level (X1) with a 20% substitution of corn flour from the total amount of wheat flour used.